Synthesis of New Derivatives of PÂ Lactam Antibiotics - Saud, M.D.; AL- Mejwel, N.F.; Sbarrad, A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New Derivatives for Known P- Jactam antibiotics were synthesized utilizing the free amino group pres nt in the parent compounds as the site for derivatization. The objectives for this study are to have new compounds which could have an increased potential resistance to the degradative enzymes knowing to be able to destroy the antibacterial activity of 13Â· lactam antibiotics- Besides. these new derivatives could be congeners of known agents, or may be a pott:ntial pro-drugs for these agents.